2011
DOI: 10.1002/cncr.26252
|View full text |Cite
|
Sign up to set email alerts
|

Reirradiation and hyperthermia for radiation‐associated sarcoma

Abstract: BACKGROUND:The objective of this study was to evaluate the role of reirradiation and hyperthermia in the treatment of radiation-associated sarcoma (RAS) in the thoracic region, which is an increasing, yet extremely rare condition with a poor prognosis. METHODS: Between 1979 and 2009, 16 patients with RAS in the thoracic region were treated in the Academic Medical Center and the Institute Verbeeten with reirradiation and hyperthermia. In 13 patients, this treatment was given for unresectable disease and 3 times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…However, complete RAAS response rates using radiotherapy with hyperthermia have been reported [23, 24]. Additionally, a recent study observed local recurrence in only 1 of 13 patients who received radiation for their RAAS versus 10 of 29 who underwent surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete RAAS response rates using radiotherapy with hyperthermia have been reported [23, 24]. Additionally, a recent study observed local recurrence in only 1 of 13 patients who received radiation for their RAAS versus 10 of 29 who underwent surgery alone.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 16 patients received irradiation with concurrent HT for the treatment of radiation-associated sarcomas (predominantly angiosarcoma) showing a total response rate of 75%. Toxicity was mild except one grade 4 adverse event (117). First clinical results show general feasibility of applying RTHT to sarcoma treatment.…”
Section: Clinical Evidence Of Combined Thermoradiotherapymentioning
confidence: 99%
“…Although, its application was quite restricted at the beginning (probably due to earlier technical difficulties in delivering heat on the tumor site) its beneficial effects were evident from early studies [106,107]. A great number of randomized phase II and III clinical trials utilizing hyperthermia have outlined its contribution in potentiating the efficiency of irradiation in treating breast [108], cervical [109], lung [110], head and neck [111], melanoma [112], gastrointestinal [113] and sarcoma cancers [114]. Furthermore, hyperthermia combined with several chemotherapeutic agents has been the subject of numerous phase II and III clinical trials.…”
Section: Hyperthermia In Clinical Practicementioning
confidence: 99%